Pain management program outcomes in veterans with chronic pain and comparison with nonveterans - Jane Jomy; Eleni G. Hapidou (Taylor & Francis Group, 2020)
Background: In Canada, 41% of veterans experience chronic pain compared to the general population (20%). Many veterans with chronic pain also have comorbid disorders such as depression and posttraumatic stress disorder (PTSD), causing increased pain interference and disability. Aim: This study aims to investigate the effectiveness of a 4-week interdisciplinary pain management program at the Michael G. DeGroote Pain Clinic in Hamilton, Ontario, Canada, and to explore differences in pain experience and treatment outcomes between veterans and nonveterans in the program. Methods: Data were obtained from psychometric measures completed by 68 veterans and 68 nonveterans enrolled in the pain management program. By matching groups for age and gender, scores were compared between veterans and nonveterans. Outcomes investigated include catastrophizing, pain traumatization, stages of change, acceptance of pain, and program satisfaction. Multivariate analysis of variance (MANOVA) was conducted to examine session (admission-discharge) and group (veteran-nonveteran) differences, and independent t tests were used to examine differences in satisfaction measures. Results: Results showed that the program was effective for all participants, with significant differences between admission and discharge on several measures. However, veterans experienced significantly greater improvements in pain catastrophizing, kinesiophobia, pain traumatization, pain acceptance, stages of change, and pain coping, compared to nonveterans (P < 0.05). Though no significant differences in program satisfaction were found between groups, case managers evaluated veterans as having achieved greater benefits from the program. Conclusion: This study presents evidence supporting the effectiveness of an interdisciplinary pain management program in addressing pain-related variables in veterans and nonveterans and provides insight into how pain management is experienced differently by veterans.